Study of Seedling Trays for Raising Seedlings with Cow Dung Biomass - Bo Zhang, Wei Zhang, Yongcai Ma (Forest Chemicals Review, 1970)
In this study, using the glass transition characteristics of lignin and cow dung as raw materials, a method for preparing a biomass seedling tray for corn transplanting without adhesive added was studied. The corn seedling tray is prepared by the method of heating and compression molding. The forming mechanism of the biomass seedling tray was revealed through the biomass seedling tray forming test combined with the electron microscope analysis. The stalk fibers in the cow dung are compressed together to form a laminated mosaic structure. The mechanical mosaic force generated by the stacking of the stalk fibers is the main strength of the seedling tray. Source: The temperature of the mold increases to make the lignin in the material reach the softening temperature. After the lignin is precipitated under the action of internal stress, it adheres to the adjacent stalk fibers to form a new whole. There are more adjacent stalk fibers, and at the same time, a lignin layer is formed outside the fiber laminated mosaic structure in the cow dung; when the material temperature is lower than the glass transition temperature of the lignin, the seedling tray is formed. Therefore, under the premise that the material can be completely filled in the mold, the lower the moisture content, the better the strength and water resistance of the porous seedling pot after molding. This study provides a new method for the functional utilization of agricultural waste.